Accountability Analysis And Financial Management Transparency (Study Case On Mosque in Subdistrict Wolo, Regency Kolaka) - Paulindini, Putri; Chairunnas, Arnadi; Triani, Neks (Politeknik Negeri Semarang, 2024)
A mosque is a public institution whose assets belong to the people entrusted to the management. The management (takmir) carries out its role based on public trust, so financial reports which are a form of responsibility for the mosque management are needed to provide evidence to the public. This research aims 1) To analyze financial reports in the mosque in Wolo sub-district, Kolaka district, is it in accordance with ISAK 35 2). This research is type qualitative research with approach descriptive that is serve data with describe or describe the phenomena that occur. With the data collection method carried out with interview observation and documentation. Interview done with head mosque and treasurer on mosque subdistrict Wolo. This research shows that the implementation of accountability Financial management at the Wolo sub-district mosque is not yet accountable because there are some mosques that are not being implemented well. This is financial management, namely the financial management of the construction of the mosque at the Nurul Yaqin Mosque (Ulu Wolo sub-district, cash balances and usage have not yet been informed because the construction has not been completed. And budget Not yet adequate and accountable financial management, although very simple, financial management is strictly sharia. Meanwhile, the implementation of transparency in financial management at the Wolo sub-district mosque is not yet transparent because at the Wolo sub-district mosque: 1) mosque Not yet serve report finance Which adequate, with the provisions of ISAK 35, the Wolo sub-district mosque only presents financial reports in the form of cash in and cash out reports while the financial position report (balance sheet), comprehensive income report, cash flow, and notes on financial reports have not been presented, 2) implementation of financial management transparency in Wolo sub-district mosques, some mosques have transparent principles but are still very simple